Solving one dimensional Bratu Type Equation using Runge-Kutta Technique and Adomian Decomposition Technique / Nur Asyikin Hashimi, Nur Izzati Abd Jamal Nasir and Nik Puteri Zakirah Nik Othman - Hashimi, Nur Asyikin; Abd Jamal, Nur Izzati; Nik Othman, Nik Puteri Zakirah (2019)
The research aims to determine the effective numerical solution of Bratu equation. Rather than calculated the exact solution, it has been solving numerically by using Runge¬ Kutta Method and Adomian Decomposition Method. Parametric study of vary lambda (,l) and step size h was conducted and had been observed. However, boundary value problem of Bratu equation is then fixed from O to 1. Hence, these two numerical techniques are then compared with the exact solution. The least absolute error significantly defines the highest accuracy.